2020
DOI: 10.1007/s12325-020-01305-1
|View full text |Cite
|
Sign up to set email alerts
|

Post-transplantation Outcomes in Patients with PA or MMA: A Review of the Literature

Abstract: Introduction: Liver transplantation is recognised as a treatment option for patients with propionic acidemia (PA) and those with methylmalonic acidemia (MMA) without renal impairment. In patients with MMA and moderate-to-severe renal impairment, combined liver-kidney transplantation is indicated. However, clinical experience of these transplantation options in patients with PA and MMA remains limited and fragmented. We undertook an overview of post-transplantation outcomes in patients with PA and MMA using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 55 publications
(74 reference statements)
0
55
0
Order By: Relevance
“…Recently a review on the literature on MMA and PA transplanted patients showed 373 transplanted patients and a mortality rate of 11% and 14%, respectively. 13 This gives a first insight of the worldwide (reported) frequency of transplantation within these specific disorders. The aim of this study was to provide an overview of all known transplanted MMA, PA, MSUD, and UCD patients in Europe in order to describe patient characteristics and global outcome (mortality at the time of the evaluationquestionnaire, frequency of peri-/postoperative complications, and whether or not cognitive development and QOL improved after transplantation) after liver and/or kidney transplantation was evaluated structurally.…”
Section: Introductionmentioning
confidence: 91%
“…Recently a review on the literature on MMA and PA transplanted patients showed 373 transplanted patients and a mortality rate of 11% and 14%, respectively. 13 This gives a first insight of the worldwide (reported) frequency of transplantation within these specific disorders. The aim of this study was to provide an overview of all known transplanted MMA, PA, MSUD, and UCD patients in Europe in order to describe patient characteristics and global outcome (mortality at the time of the evaluationquestionnaire, frequency of peri-/postoperative complications, and whether or not cognitive development and QOL improved after transplantation) after liver and/or kidney transplantation was evaluated structurally.…”
Section: Introductionmentioning
confidence: 91%
“…Yap et al recently performed a similar analysis, concluding that transplantation procedures in MMA and PA patients have potential benefits as well as associated risks. 74 We suggest considering the management flowchart for MMA and PA patients undergoing general anaesthesia provided in Figure 4, when performing any transplantation procedure.…”
Section: T a B L E 4 Emergency Regimensmentioning
confidence: 99%
“…Recently, medical management with dietary protein restriction has been improved; however, the risk of poor neurological outcomes and progressive renal dysfunction can be inevitable particularly for severe MMA cases. During the past decade, an increasing number of MMA patients received liver or combined liver/kidney transplant and favorable biochemical outcomes have been reported [ 8 , 14 , 15 , 16 , 17 ]. Consistent with the previously reported transplanted cases, our patients showed significant improvements in their plasma methylmalonic acid level after LT.…”
Section: Discussionmentioning
confidence: 99%